2021
DOI: 10.1111/jpc.15435
|View full text |Cite
|
Sign up to set email alerts
|

Rectum sizes: Assessment by ultrasonography in children with functional constipation

Abstract: Aim This study aimed to compare the transverse diameter and thickness of the anterior wall of the rectum in children with normal bowel movement and children with functional constipation in different age groups. Another objective was to find correlations of rectum sizes with faecal incontinence and constipation duration. Methods In the study, we included children with normal bowel movement and functional constipation diagnosed based on the Rome III and Rome IV criteria. We collected clinical data from the paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 21 publications
9
16
1
Order By: Relevance
“…In their study, the mean duration of constipation was 29 months. Similar to our study, Pop et al 29 found a positive correlation between RTD and the duration of constipation. Pop et al 29 and de Abreu et al 30 also found a significant association between RTD and faecal incontinence, although this was not seen in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In their study, the mean duration of constipation was 29 months. Similar to our study, Pop et al 29 found a positive correlation between RTD and the duration of constipation. Pop et al 29 and de Abreu et al 30 also found a significant association between RTD and faecal incontinence, although this was not seen in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, Pop et al 29 found a positive correlation between RTD and the duration of constipation. Pop et al 29 and de Abreu et al 30 also found a significant association between RTD and faecal incontinence, although this was not seen in our study. Previous studies have shown an inverse association between the frequency of defaecation with RTD and RAWT, 26,28 which is consistent with the results of our survey.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 12 In another study, re-evaluated rectal diameters after constipation treatment showed that measurements decreased after 4 weeks of polyethylene glycol treatment. 20 However, we could not re-evaluate our patients’ rectal diameter measurements after constipation treatment.…”
Section: Discussionmentioning
confidence: 96%
“…As the patients got older, the difference between them was smaller but still significant. 12 Doniger et al 19 and Pop et al 20 found a strong correlation between enlarged transrectal diameter and constipation. When rectal diameter was measured in the axial plane, it was found to be 31.72 ± 6.93 mm in the constipated patient group and 19.85 ± 4.37 mm in the control group ( P = .001).…”
Section: Discussionmentioning
confidence: 97%